Streptococcus gallolyticus supernatant induces M2 macrophage polarization and activates IL-17 F signaling in colorectal tumorigenesis - Jiaqi Wang; Yan Zhang; Duo Luo; Jing Xu; Xin Nie; Chen Huang; Hailan Zhao; Minzheng Zhu; Xue Guo; Yong Zhang; Wenjing Qiu; Haoming Xu; et al. (Gut Pathogens)
Abstract Background Colorectal cancer (CRC) is a prevalent global malignancy where gut microbiota plays a key role. Streptococcus gallolyticus (Sg), a gut commensal and opportunistic pathogen, is associated with CRC. This study investigates the impact of the supernatant derived from Sg cultures (hereafter referred to as Sgsup) on CRC progression and examines the underlying mechanisms. Methods Quantitative PCR (qPCR) was employed to assess Sg colonization in paired tumors and adjacent normal tissues from 46 CRC patients. CRC cell lines (HCT116, HT29) were treated with Sgsup, and cell proliferation was measured using the CCK-8 assay. Non-targeted metabolomic profiling of Sgsup was performed via liquid chromatography-mass spectrometry (LC-MS). An azoxymethane/dextran sulfate sodium (AOM/DSS)-induced mouse model of CRC was used to evaluate in vivo tumor burden, inflammation, and macrophage polarization (flow cytometry). Transcriptomic analysis via RNA-seq was conducted to identify enriched signaling pathways. Results The detection rate of Sg was significantly higher in tumor tissues compared to adjacent tissues (47.8% vs. 30.4%, P < 0.01). Sgsup significantly increased CRC cell proliferation (P < 0.05). Non-targeted metabolomic analysis revealed an enrichment of metabolites, including inosine monophosphate (IMP), methionine, uridine, and creatine in Sgsup. In vivo, Sgsup increased tumor number/burden (P < 0.05), elevated inflammation scores (P < 0.05), and shortened colon length. Flow cytometry indicated that Sgsup promoted M2 macrophage polarization (as evidenced by increased CD206+ cells and reduced M1/M2 ratio). RNA-seq demonstrated significant enrichment of the IL-17 signaling pathway, with upregulated expression of IL-17 F and IL-22 (P < 0.05). Conclusion Sgsup is associated with CRC progression by promoting cell proliferation and inflammation, facilitating M2 macrophage polarization, and elevating IL-17 F and IL-22 expression. Metabolites such as creatine, along with IL-17 F/IL-22-related signaling pathways, appear to be involved. These findings suggest that both Sg-derived metabolites and host immune signaling may serve as potential targets for CRC intervention. Functional validation of individual metabolites is currently in progress.